2022
DOI: 10.1002/adma.202109445
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Chemical Functionalization of Top‐Contact Electrodes: Tuning the Charge Injection for High‐Performance MoS2 Field‐Effect Transistors and Schottky Diodes

Abstract: The fabrication of high‐performance (opto‐)electronic devices based on 2D channel materials requires the optimization of the charge injection at electrode–semiconductor interfaces. While chemical functionalization with chemisorbed self‐assembled monolayers has been extensively exploited to adjust the work function of metallic electrodes in bottom‐contact devices, such a strategy has not been demonstrated for the top‐contact configuration, despite the latter being known to offer enhanced charge‐injection charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Han et al reported the use of molecular functionalization to change the work function of gold electrodes. Then, they fabricated top-contact FETs via the transfer of these pre-modified electrodes to tune the charge injection in MoS 2 FETs [ 32 ], demonstrating the modulation of the Schottky barrier. This method has also been used in 2D-materials-based resistive random-access memory, leading to a stable resistive switching performance [ 33 ].…”
Section: Contact Engineering Of 2d Fetsmentioning
confidence: 99%
“…Han et al reported the use of molecular functionalization to change the work function of gold electrodes. Then, they fabricated top-contact FETs via the transfer of these pre-modified electrodes to tune the charge injection in MoS 2 FETs [ 32 ], demonstrating the modulation of the Schottky barrier. This method has also been used in 2D-materials-based resistive random-access memory, leading to a stable resistive switching performance [ 33 ].…”
Section: Contact Engineering Of 2d Fetsmentioning
confidence: 99%
“…Figure S2a,d show the optical microscopy images of monolayer MoS 2 , while Figure S1 displays the AFM topographical image. The pristine monolayer MoS 2 crystal exhibits an atomically flat surface with a root-mean-square roughness ( R RMS ) of approximately 0.5 nm, due to its easy-to-peel van der Waals layered structure and the absence of dangling bonds on the surface. , Figure S2b and e confirm the absence of changes in the thickness and roughness of MoS 2 upon the introduction of defects. However, after molecular functionalization, a considerable increase in the average thickness of the MoS 2 monolayer has been observed.…”
Section: Resultsmentioning
confidence: 61%
“…We counted dozens of devices and found that after functionalizing with 26DFBT, the V th decreased by 20.3 ± 6.3 V, while the V th increased by 18.8 ± 8.5 V after functionalizing with 35DFBT. The charge in the carrier density change (Δ n ) within the channel can be quantified by the change of V th with the equation below: Δ n = C o x Δ V th e = ε o x Δ V th t o x e = 7.99 × 10 10 Δ V th cm 2 where C ox is the capacitance per unit area of dielectric layer, Δ V th is the change of V th , e is the elementary charge, ε ox is the dielectric constant of the dielectric layer, and t ox is the thickness of dielectric layer. The value of Δ n is indicative of the molecule’s dipole-induced doping capability.…”
Section: Resultsmentioning
confidence: 99%
“…In another device with a trilayer flake with 7 fingered device, as shown in Figure S12, also showed a gate dependency with the longitudinal resistance R xx = 108–119 kΩ at V G = 30 V. The resistance is relatively small and the estimated contact resistance is ∼100 kΩ. The issues on the high contact resistance are still in challenge to realize 2D electronics. …”
Section: Resultsmentioning
confidence: 98%